A Prototype Development Of Anti-Hunchback Device - Ab Rahman, Mohd Hidayat; Maidin, Nurul Ain; Ahmad, Mohd Nazri; Osman, Mohd Hairizal; Wahid, Mohammad Khalid; Hussin, Mohamed Saiful Firdaus; Mohd Yassim, Halyani; Razali, Muhammad Zayani Afiq (Universiti Teknologi MARA, 2018)
The spine is a part of our body which is very important but often neglected.Sometimes because of our own mistakes,the damage or injury in the spine will cause a variety of problems that have to be borne.Therefore,the objective of this research is to develop a device that is able to warn by triggering people about the position of the spine body if the hunch exceed the critical level by vibration.This device is environmentally friendly and small in size.In the process of making 'Anti Hunchback Device’,observations have been made against those who tend towards the hunchback problems.Taking data from the user by questionnaire and using product design and development method to produce this device.This device will be a useful solution to address the problem of bone bent at an early stage of the spine disease,restoring a healthy posture health care for the long term and also save money from health spending for the foreseeable future.